On the Present and the Past of Pandemics - Diego Armus (Wolters Kluwer Health/LWW, 2023)
During the COVID-19 pandemic, a multitude of narratives saturated the print, audiovisual, and electronic media. Improvised, uninformed, apocalyptic and voluntarist approaches abounded. These notes - written during the pandemic and delivered in the conference series - address the proliferation of such discourses, emphasizing a series of issues. First, the widespread ignorance about the history of epidemics. Then, the inability to deal with the uncertainties that reign during pandemic times, as well as the announcements that this extraordinary health/sanitary event would produce a profound watershed in all walks of life and in all corners of the world. Finally, and against the general assertion that "one learns from the past to understand the present," these notes seek to point out how the present can illuminate the study of the past - or, more personally, what I think I have learned as a historian in the times of the COVID-19 pandemic.